Temperature-Dependent Optical Absorption Study of Exciton Binding Energy in Organolead Halide Perovskites - Gagik Ayvazyan; Harutyun Dashtoyan; Surik Khudaverdyan; Lenrik Matevosyan; Ashok Vaseashta (IEEE Access)
Organolead halide perovskites have recently garnered significant attention for their potential in solar cell applications, as well as their promise for light-emitting and lasing devices. In this study, we investigate the excitonic and electronic properties of mixed halide organolead perovskite CH3NH3PbCl ${}_{3\text {-}\text {x}}$ Ix layers through temperature-dependent optical absorption spectroscopy. By analyzing spectral features across the 77–300 K range, we determined the exciton binding energy ( $E_{b} ≈ ~14$ meV) and the bandgap energy. The experimentally derived $E_{b}$ , obtained from absorption-edge shifts, is nearly half the theoretical value calculated using the Wannier–Mott model with a high-frequency dielectric constant ( $ε _{∞ } =6.55$ ). The $E_{b}$ values close to the thermal energy at room temperature, confirmed by both the experimental and theoretical approaches, indicate predominantly non-excitonic behavior, with approximately 95% of excitons dissociating into free carriers, which is essential for high photovoltaic efficiency. A discontinuity in the bandgap (from 1.57 eV to 1.72 eV) near 150–160 K reflects the impact of the tetragonal-to-orthorhombic phase transition on the material’s optoelectronic properties. While a more accurate treatment of dielectric screening, for example through in situ studies or by considering effective dielectric constants ( $ε _{eff} ≈ ~10$ ), is needed, our results quantitatively confirm the weakly bound excitonic character of mixed-halide perovskites under operational conditions. These findings provide useful insights for their optimized design in solar energy applications.